Postgraduate diploma in teaching and learning - Universiti Malaysia Sarawak, Centre for Applied Learning and Multimedia (Universiti Malaysia Sarawak (UNIMAS), 2014)
The objectives of the Postgraduate Diploma in Teaching and Learning programme are to: i. train UNIMAS academics in teaching and learning on a systematic and formal basis to enhance their personal competence as university educators; ii. establish a long term commitment toward teaching and learning that is consistent with UNIMAS teaching and learning policies; and iii. develop a culture of collaborative academic environment that places special commitment to excellence in teaching and learning.